The Increasing Compassion Through Storytelling Method - Agustina Agustina; Salma Talitha Qushayyi; Utari Nur Cahyani; Juwarti Juwarti; Ratna Wahyu Pusari (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
This study aims to foster a sense of compassion in young children through storytelling at the Daarul Huda Islamic Kindergarten. The study was motivated by the low levels of empathy and social acceptance shown by children towards their peers, particularly those with special needs. The study employed the Classroom Action Research (CAR) method, conducted over two cycles. The research subjects comprised seven children aged 4–5 years. Data collection techniques included observation, interviews, and documentation. The data were analysed using both qualitative and quantitative descriptive methods. The results of the study indicate that the storytelling method is effective in enhancing children’s sense of compassion. In the pre-cycle, 85.71% of the children were in the ‘Beginning to Develop’ category and 14.29% in the ‘Developing as Expected’ category. Following the intervention in Cycle I, the proportion in the ‘Developing as Expected’ category increased to 85.71%. In Cycle II, all children achieved the ‘Developing Very Well’ category (100%). Improvements were observed in the children’s ability to speak politely, help friends, share, understand others’ feelings, and demonstrate caring behaviour. Thus, the storytelling method is effective for developing the social-emotional skills of young children